“PRESERVING SAMARKAND’S HISTORICAL URBAN ENVIRONMENT AMID MODERN DEVELOPMENT” - Nuriddinova Diyora Jasurbek Qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the challenges and strategies for preserving Samarkand’s historical urban environment while accommodating contemporary development. The study focuses on the interaction between historical monuments such as Registan Square, Shah-i-Zinda, and Gur-e Amir Mausoleum and modern urban structures, including hotels, commercial buildings, and public spaces. The research highlights methods to maintain aesthetic and cultural harmony while supporting urban growth and modern infrastructure.